The Formative Leadership of Administrators in School Under Nakhon Pathom Primary Educational Service Area 2 - Pathumpraikhajorn, Pimnara; Thitapunno, Dr., Phramaha Thamrong (Journal of Dhamma for Life, 2024)
This research article aims; 1) to study the creative leadership of school administration under the Nakhon Pathom Primary Educational Service Area Office, Area 2. 2) To study administration in educational institutions. Under the jurisdiction of the Nakhon Pathom Primary Educational Service Area Office, Area 2. 3) To study the creative leadership of educational institution administrators that affects administration in educational institutions under the Nakhon Pathom Primary Educational Service Area Office, Area 2. The research sample consists of 92 schools under the jurisdiction of the Educational Service Area Office, Area 2, Nakhon Pathom Primary Education Office, with data collected from 552 participants. The research utilized a questionnaire as the data collection tool and employed pre-built statistical programs for data analysis. Statistical methods used for analysis included Frequency, Percentage, Arithmetic Mean, Standard Deviation, and Stepwise Multiple Regression Analysis. The research findings indicate that the analysis of the creative leadership qualities of school administrators affiliated with the Educational Service Area Office, Area 2, Nakhon Pathom Primary Education Office, is generally at a very high level. When considering specific aspects, the highest levels were observed in Vision, Emotional Intelligence, and Flexibility, in that order. Regarding the analysis of management practices in educational institutions under the supervision of the Educational Service Area Office, Area 2, Nakhon Pathom Primary Education Office, overall performance was rated as very high. In specific areas, the highest levels were observed in General Management, Budget Management, Personnel Management, and Academic Management, respectively. The creative leadership qualities of school administrators were found to significantly influence the management of educational institutions, particularly in the area of flexibility, with a predictive efficiency of 12.2%. The prediction has a coefficient of 0.142. The predictive equations in raw scores and standardized scores are Ŷtot = 3.858** + .202**(X2) and Z^’ = .349**(X2), respectively.